2011
DOI: 10.1161/circresaha.111.242974
|View full text |Cite
|
Sign up to set email alerts
|

Disease Pathways and Novel Therapeutic Targets in Hypertrophic Cardiomyopathy

Abstract: As described in earlier reviews in this series on the molecular basis of hypertrophic cardiomyopathy (HCM), HCM is one of the archetypal monogenic cardiovascular disorders to be understood at the molecular level. Twenty years after the discovery of the first HCM disease gene, genetic studies still confirm that HCM is principally a disease of the sarcomere. At the biophysical level, myofilament mutations generally enhance Ca 2+ sensitivity, maximal force production, and ATPase activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
135
1
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(142 citation statements)
references
References 126 publications
(127 reference statements)
2
135
1
2
Order By: Relevance
“…In the modern era, specific pathophysiological HCM derangements have been targeted in the preclinical realm, and trials are beginning in patients 15,87,88 . Targeting cellular energetic impairment is a promising paradigm in HCM.…”
Section: [H1] Treatment Of Energy Depletionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the modern era, specific pathophysiological HCM derangements have been targeted in the preclinical realm, and trials are beginning in patients 15,87,88 . Targeting cellular energetic impairment is a promising paradigm in HCM.…”
Section: [H1] Treatment Of Energy Depletionmentioning
confidence: 99%
“…In this Perspectives article, we focus primarily on the energy depletion hypothesis, but we also summarize the evidence for Ca 2+ sensitization, and discuss how the two theories overlap. Increasing evidence indicates that energy depletion has an important role in the development of hypertrophy and in the wider pathophysiology of HCM [9][10][11][12][13][14][15] . We summarize this evidence, and then discuss the phenotypic manifestations of energy depletion in three realms of cardiac function: diastolic dysfunction, dynamic systolic dysfunction (especially against imposed afterload), and arrhythmogenesis.…”
mentioning
confidence: 99%
“…This suggested that CD36 depletion reduces SR Ca 2ϩ reuptake delaying Ca 2ϩ clearance. This would diminish ability of cells to regulate and synchronize beating frequency (35,36).…”
Section: Cd36 Knockdown Impairs Sr Ca 2ϩ Uptake In Cardiomyocytes-promentioning
confidence: 99%
“…2ϩ Handling-Cytosolic Ca 2ϩ reuptake by the SR in preparation for the next excitation is accomplished by the ATPase (SERCA) enzyme, which is tightly regulated via interaction with its inhibitor PLN (35). Phosphorylation of PLN by protein kinase A (PKA) reverses the inhibition and increases SERCA activity and the rate of SR Ca 2ϩ uptake (56).…”
Section: Cd36 Deficiency Markedly Alters Levels Of Myocardial Proteinmentioning
confidence: 99%
See 1 more Smart Citation